Creating Compositional Community in Your Classroom. (March 2016) - Stringham, David A.
In performance-focused ensemble classrooms, students and teachers often work toward convergent solutions (e.g., accurate notes and rhythms, agreeing on interpretation). Hierarchical structures may be in place in which it is considered inappropriate to question or disagree with an interpretation set forth by the leader. Teaching composition, in contrast, calls for both peers and teachers to stimulate divergent thinking that draws out a composer's expressive intentions and compositional craftsmanship. This type of environment may be less familiar to those who have spent considerable time in performance-centered contexts. This article offers strategies for creating a supportive, safe, and collaborative community in which students and teachers share compositions, provide feedback, promote critical thinking, and encourage composers in developing and performing their work.